The cult of the Virgin Mary in medieval Italy : art, devotion, and liturgy in Orvieto - James, Sara Nair (Cambridge University Press, 2025)
"Focusing on two fourteenth-century narrative programs in the tribune of Orvieto Cathedral: Giovanni di Bonino's stained-glass window and Ugolino di Prete Ilario's frescoes, this book explores the mysterious allure of the Virgin Mary and the manifestation of her cult in Italy. It shows how the narratives promoted agendas tied to the city's history"--